2022
DOI: 10.1021/acsanm.2c02028
|View full text |Cite
|
Sign up to set email alerts
|

MoS2 and WS2 Nanosheets Decorated on Metal–Organic Framework-Derived Cobalt/Carbon Nanostructures as Electrocatalysts for Hydrogen Evolution

Abstract: The replacement of platinum with nonprecious metal electrocatalysts for hydrogen evolution reaction (HER) remains an important challenge. We report facile synthesis of precious-metal-free HER electrocatalysts that are made up of metal–organic framework-derived cobalt/carbon nanostructures and semicrystalline ultrathin MoS2 or WS2 nanosheets. The as-synthesized catalysts MoS2/Co@NC and WS2/Co@NC delivered an electrochemical HER current density of 25 mA cm–2 at overpotentials of 0.23 and 0.28 V, respectively. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…[ 78 ] For MoS 2 layers doped with Co NCs, the DFT results showed that the CoMo interface served as preferred active centers, not only enhancing the catalytic activity of per unit active site but also improving the basal plane activity of original MoS 2 (Figure 4b, c). [ 79 ] In another work, when highly dispersed Pt NCs are loaded on the active‐site‐rich ultrathin SnS 2 , PtSn sites can significantly lower the reaction energy barrier for the HER reaction. [ 80 ] Also, by applying the first principle calculations, the atomic M 4 cluster on MN 4 ‐graphene substrate (M = Fe, Ni) is investigated, and the obtained heterometallic Ni 4 @FeN 4 ‐Gr lead to enhanced HER activity.…”
Section: Approaches To Superior Her Performancementioning
confidence: 99%
See 1 more Smart Citation
“…[ 78 ] For MoS 2 layers doped with Co NCs, the DFT results showed that the CoMo interface served as preferred active centers, not only enhancing the catalytic activity of per unit active site but also improving the basal plane activity of original MoS 2 (Figure 4b, c). [ 79 ] In another work, when highly dispersed Pt NCs are loaded on the active‐site‐rich ultrathin SnS 2 , PtSn sites can significantly lower the reaction energy barrier for the HER reaction. [ 80 ] Also, by applying the first principle calculations, the atomic M 4 cluster on MN 4 ‐graphene substrate (M = Fe, Ni) is investigated, and the obtained heterometallic Ni 4 @FeN 4 ‐Gr lead to enhanced HER activity.…”
Section: Approaches To Superior Her Performancementioning
confidence: 99%
“…b) LSVs, c) The calculated Gibbs free energy. Reproduced with permission [79]. Copyright 2022, American Chemical Society.…”
mentioning
confidence: 99%
“…As a result of their diversied and tunable nanostructures, porous MOFs have been regarded as emerging precursors for the facile syntheses of single metal sites or metal compounds (such as oxides, phosphides, suldes, selenides and others), as well as their composites for electrochemical catalysis. [178][179][180][181] On the other hand, compared with other types of MOF derivatives, multifunctional CNMs are structurally endowed with high hydrophobicity due to low polarity caused by the high graphitization degree, which greatly hinders the mass transfer and conduction process of electrocatalytic materials in a liquid. This is a common problem for MOFderived CNMs, and is also the most urgent problem to be solved at present.…”
Section: Electrocatalysismentioning
confidence: 99%
“…Except for the carbon template, the MOF derivatives can also provide metal source to construct bimetallic or polymetallic dichalcogenide to regulate the active components in the composites [136–143] . In an inert atmosphere, PB‐based nanocubes can be pyrolyzed to nitrogen‐doped porous nanocubic structures with metal sites (FeCN or FeCo@C).…”
Section: Synthesis Of 2d MX Composite Based On Metal‐organic Assembly...mentioning
confidence: 99%